Genotypic Determination of Extended Spectrum β-Lactamases and Carbapenemase Production in Clinical Isolates of Klebsiella pneumoniae in Southwest Nigeria - Gbolabo Odewale; Motunrayo Yemisi Jibola-Shittu; Olusola Ojurongbe; Rita Ayanbolade Olowe; Olugbenga Adekunle Olowe (MDPI AG, 2023)
Introduction: Klebsiella pneumoniae is a major pathogen implicated in healthcare-associated infections. Extended-spectrum β-lactamase (ESBL) and carbapenemase-producing K. pneumoniae isolates are a public health concern. This study investigated the existence of some ESBL and carbapenemase genes among clinical isolates of K. pneumoniae in Southwest Nigeria and additionally determined their circulating clones. Materials and Methods: Various clinical samples from 420 patients from seven tertiary hospitals within Southwestern Nigeria were processed between February 2018 and July 2019. These samples were cultured on blood agar and MacConkey agar, and the isolated bacteria were identified by Microbact GNB 12E. All K. pneumoniae were confirmed by polymerase chain reaction (PCR) using the 16s rRNA gene. Antibiotic susceptibility testing (AST) was done on these isolates, and the PCR was used to evaluate the common ESBL-encoding genes and carbapenem resistance genes. Genotyping was performed using multi-locus sequencing typing (MLST). Results: The overall prevalence of K. pneumoniae in Southwestern Nigeria was 30.5%. The AST revealed high resistance rates to tetracyclines (67.2%), oxacillin (61.7%), ampicillin (60.2%), ciprofloxacin (58.6%), chloramphenicol (56.3%), and lowest resistance to meropenem (43.0%). All isolates were susceptible to polymyxin B. The most prevalent ESBL gene was the TEM gene (47.7%), followed by CTX-M (43.8%), SHV (39.8%), OXA (27.3%), CTX-M-15 (19.5%), CTX-M-2 (11.1%), and CTX-M-9 (10.9%). Among the carbapenemase genes studied, the VIM gene (43.0%) was most detected, followed by OXA-48 (28.9%), IMP (22.7%), NDM (17.2%), KPC (13.3%), CMY (11.7%), and FOX (9.4%). GIM and SPM genes were not detected. MLST identified six different sequence types (STs) in this study. The most dominant ST was ST307 (50%, 5/10), while ST258, ST11, ST147, ST15, and ST321 had (10%, 1/10) each. Conclusion: High antimicrobial resistance in K. pneumoniae is a clear and present danger for managing infections in Nigeria. Additionally, the dominance of a successful international ST307 clone highlights the importance of ensuring that genomic surveillance remains a priority in the hospital environment in Nigeria.